IMPLEMENTASI SUPERVISI PENDIDIKAN DALAM MENINGKATKAN PROSES PEMBELAJARAN DI MIN SUKADAMAI KOTA BANDA ACEH - Cut Suryani (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2015)
A principal as a supervisor has to conduct supervision in his/her school. Hence he/she must be able to perform a variety of monitoring and control to improve the performance of teachers. Supervision and control are preventive ways to prevent teachers to do irregularities and thus will be more careful in carrying out his work as educators. This research is intended to study supervision activities performed by principal of Islamic Elementary School (Madrasah Ibtidaiyah Negeri (MIN)) Sukadamai Banda Aceh. The results of this research show several findings: 1). The focus of supervision activities performed by principal can be identified in two things i.e supervision activities concerning the teachers’ administration and teachers’ teaching practices; 2). Supervision activity is useful for teachers to solve educational problems at the time of learning, and to provide motivation for them to improve the knowledge to become professionals in teaching and learning process; 3). Principal’s barriers in supervision consists of overlapping activities and lack of operational budget.